1976
DOI: 10.1073/pnas.73.5.1674
|View full text |Cite
|
Sign up to set email alerts
|

Changes in type of collagen synthesized as clones of chick chondrocytes grow and eventually lose division capacity.

Abstract: Clones of embryonic chick chondrocytes have been isolated and collagen biosynthesis has been followed as the clones grow and eventually lose division capacity. Analysis of collagen type at each successive subculture until the time of cellular senescence has shown that a change in synthesis occurs from the cartilage-specific Type II collagen (chain composition Ial(II)H) to a mixture of Type I collagen (chain composition [al(I) MATERIALS AND METHODS Materials. F-10 medium containing twice the usual concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
160
1
2

Year Published

1978
1978
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(169 citation statements)
references
References 22 publications
6
160
1
2
Order By: Relevance
“…Studies that have examined the plasticity of the chondrocyte phenotype from many different species have consistently shown that culture of these cells in monolayers on plastic substrata for prolonged periods or upon repeated passages leads to the loss of their spherical shape and to the acquisition of an elongated fibroblast-like morphology (7,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). These morphologic alterations are accompanied by profound biochemical changes, including loss of the cartilage-specific phenotype, as evidenced by an arrest of the synthesis of the cartilage-specific collagens (types II, IX, and XI) and proteoglycans (aggrecan), initiation of synthesis of the interstitial collagens (types I, III, and V), and increase in the synthesis of fibroblasttype proteoglycans (versican) at the expense of aggrecan (7,17,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…Studies that have examined the plasticity of the chondrocyte phenotype from many different species have consistently shown that culture of these cells in monolayers on plastic substrata for prolonged periods or upon repeated passages leads to the loss of their spherical shape and to the acquisition of an elongated fibroblast-like morphology (7,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). These morphologic alterations are accompanied by profound biochemical changes, including loss of the cartilage-specific phenotype, as evidenced by an arrest of the synthesis of the cartilage-specific collagens (types II, IX, and XI) and proteoglycans (aggrecan), initiation of synthesis of the interstitial collagens (types I, III, and V), and increase in the synthesis of fibroblasttype proteoglycans (versican) at the expense of aggrecan (7,17,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…Another frequently found phenomenon is the expression of structures and chemical compounds in the cultured cell that are not found in the cell in situ. Typical examples include the formation of collagen type I in chondrocytes (24) and of intermediate-sized filaments of the vimentin type in cultured cells from epithelial, neuronal, and muscle origin (e.g., see references 2, 11, and 12).…”
mentioning
confidence: 99%
“…Similar results have also been obtained with CaC12 [5], suggesting that the local increase in calcium or pyrophosphate ions around the chondrocytes stimulates them to produce type I collagen. The clones of chick embryonic chondrocytes switch their synthesis of collagen from type II to type I and type I trimer, as a result of aging in culture [4]. One chondrocyte, therefore, has the capability of synthesizing more than one type of collagen molecule.…”
Section: Resultsmentioning
confidence: 99%
“…The cartilage undergoing osteoarthritic changes, as well as normal aged cartilage, produces type I collagen (composed of two al (I) and one a2 chains) in addition to the tissue-specific type II collagen [1][2][3]. Chick-embryonic chondrocytes, when subcultured to senescence, synthesize type I collagen and type I trimer rather than type II collagen [4]. The chondrocytes from normal rabbitarticular cartilage switch their phenotypic expression to type I collagen when isolated from the tissue and maintained in monolayer culture [5][6][7].…”
Section: Introductionmentioning
confidence: 99%